Nuclear energy - Haney, Johannah (Marshall Cavendish Benchmark, 2013)
Natural resources are disappearing fast in order to power our high-tech world. Will nuclear energy be one of the main answers to the environmental crisis at hand? Examine the science behind nuclear energy, as well as the issues that challenge more widespread use.